Psychological Well-Being of Social Workers in Government Agencies and Social Service Foundations - Della Nur Shayidah; Dhian Riskiana Putri; Sri Ernawati (Psikostudia : Jurnal Psikologi, 2026)
Social workers face job challenges and emotional pressures that can potentially affect their psychological well-being. This study aims to explore the psychological well-being of social workers in local government agencies or social service foundations in Sragen Regency. The method used in this study is descriptive qualitative with data collection through in-depth interviews and observations of five social workers and two supporting informants. The data were analyzed systematically through data reduction, data presentation, and verification of findings to identify the main themes. The results of this study indicate that social workers show the ability to accept themselves, interpret their work as a source of meaning in life, manage work demands, and obtain social support that helps maintain their psychological well-being. These results indicate that the psychological well-being of social workers is relatively good and is influenced by personal factors, social support, and the ability to adapt to various work demands. These findings are expected to form the basis for the development of programs and policies that support the psychological well-being of social workers.